PROBLEMS OF AUTHORITY OF LAND DEED MAKING OFFICIALS IN THE TRANSFER OF RIGHTS IN SURABAYA - Ika Sulistiyowati; Prasetijo Rijadi (Fakultas Hukum Universitas Bhayangkara Surabaya, 2024)
Population and economic growth have given rise to excesses in terms of ownership of land rights and obligations, whether social or individual. In this case, the government seeks to overcome various problems that arise by arranging this most strategic problem by affirming the legal certainty of land rights and obligations, a land registration process is needed. This research uses normative juridical methods, namely legal research conducted by examining library or secondary materials as basic materials which are then examined by conducting searches on regulations and legal materials related to the problems studied. The study concluded that PPAT has an important role in the transfer of rights, namely making authentic deeds regarding legal acts of transfer of rights which are then used as the basis for land registration. In the process of transferring rights, of course, it is related to BPHTB or Land Rights Acquisition Duty, which is the obligation to pay taxes for buyers due to the acquisition of land rights. PPAT in making a deed of sale and purchase of PPAT must ensure that all tax payment obligations must have been paid in full by the taxpayer, because before the tax wajin pays in full its tax obligations, PPAT must not make and sign the deed of transfer of rights. This is in accordance with the provisions of article 24 paragraph (1) of BPHTB Law No. 20 of 2000. If PPAT violates these provisions, PPAT will be subject to a penalty of Rp. 7,500,000.00 according to article 26 of BPHTB Law No. 20 of 2000.